2014
DOI: 10.18632/oncotarget.2557
|View full text |Cite
|
Sign up to set email alerts
|

Ret finger protein-like 3 promotes tumor cell growth by activating telomerase reverse transcriptase expression in human lung cancer cells

Abstract: In this study, we identified ret finger protein-like 3 (RFPL3) as a hTERT promoter binding protein in lung cancer cells. The high hTERT promoter-binding activity of RFPL3 was detected in lung cancer cells compared to normal cells. Chromatin immunoprecipitation confirmed RFPL3 as a tumor-specific hTERT promoter binding protein. Overexpression of RFPL3 activated hTERT promoter and up-regulated hTERT expression and telomerase activity. Inhibition of RFPL3 expression by siRNA suppressed hTERT promoter activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“… 52 A number of factors have been identified to regulate the activity of the hTERT promoter directly or indirectly. 53 , 54 , 55 To test if KMT2A anchored at the hTERT promoter to regulate its expression, ChIP assay was performed in melanoma cells. The results showed that the hTERT promoter region was amplified by PCR from the complexes immunoprecipitated by the antibody against KMT2A, but not from the complexes precipitated by the IgG negative control ( Figure 2e and f ).…”
Section: Resultsmentioning
confidence: 99%
“… 52 A number of factors have been identified to regulate the activity of the hTERT promoter directly or indirectly. 53 , 54 , 55 To test if KMT2A anchored at the hTERT promoter to regulate its expression, ChIP assay was performed in melanoma cells. The results showed that the hTERT promoter region was amplified by PCR from the complexes immunoprecipitated by the antibody against KMT2A, but not from the complexes precipitated by the IgG negative control ( Figure 2e and f ).…”
Section: Resultsmentioning
confidence: 99%
“…Since hTERT was approved to be involved in the growth of lung cancer cells [ 19 ], and RFPL3 and CBP had been shown to be able to up-regulate hTERT expression, we next tested the coordinated effect of RFPL3 and CBP on cell proliferation in lung cancer cells. The H1299 cells with RFPL3-stable overexpression were transfected with CBP-specific siRNA or treated with CBP inhibitor C464.…”
Section: Resultsmentioning
confidence: 99%
“…However, little is known about the underlying molecular mechanisms of the reactivation of hTERT during tumorigenesis for lung cancers. In our previous study, we discovered and identified RFPL3 as a novel hTERT promoter-binding protein which could upregulate hTERT activity in lung cancers [ 19 ]. We also showed that the inhibition of RFPL3 expression significantly suppressed lung cancer cell growth in vitro and in a xenograft mouse model in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Next, we tested whether RBFOX3 bound to the hTERT promoter by interacting with other transcription factors. To test this hypothesis, four hTERT promoter-binding proteins KLF4 25 , RFPL3 26 , CPSF4 27 and AP-2β 23 previously identified were tested using their corresponding specific antibodies by a co-immunoprecipitation assay in the flag-RBFOX3 overexpressing Hep3B and HepG2 cells. Surprisingly, RBFOX3 could be pulled down by anti-AP-2β antibody ( Figure 6 A ).…”
Section: Resultsmentioning
confidence: 99%